Reimagining Access Rights - Jonathan Peters (Washington University Journal of Law & Policy, 2021)
Lawsuits against public record requestors have been on-going over the last 27 years and are currently on the rise. Government officials argue it is best for the courts to step in immediately if an agency’s disclosure obligations are unclear. Peters analyzes the dangers of these suits which present a clear risk to the free flow of information necessary for the press and the public. Peters examines the current patchwork of access rights derived from norms, FOI laws, state constitutional provisions, common law principles, administrative regulations, statutory privileges, and the First Amendment. Peters argues that a reimagined First Amendment right to receive information is needed to compel reliable access to the government and reduce frustration for citizens. This Article proposes finding a general First Amendment right of access to government records, meetings, places, and events.
Keywords: Public records; requests; public records requests; disclosure; disclosure obligations; information; freedom of information; FOIA; Freedom of Information Act; access; access rights; First Amendment